A Guide to Planting Wildflower Enhancements in Florida - Mary C. Bammer; Josh Campbell; Chase B. Kimmel; James D.. Ellis; Jaret C. Daniels (EDIS)
The establishment of native wildflower plantings in Florida can benefit agricultural producers as well as native pollinators and other beneficial insects (predators and parasitoids). The plantings do this by: